Institutionalizing health technology assessment in Egypt: Situational analysis and roadmap - Pilar Pinilla-Dominguez; Pilar Pinilla-Dominguez; Shorouk Taha; Hugh McGuire; Ahmed Elagamy; Amal Sedrak; Amal Sedrak; Mary Gamal; Mariam Eldebeiky; Dalia Dawoud; Dalia Dawoud (Frontiers Media S.A., 2022)
Objective: To conduct a situational analysis with the aim to inform future health technology assessment efforts (HTA) in Egypt.Introduction: The Egyptian government has set universal health coverage as a 2030 target. Several agencies have been created in the context of the ongoing healthcare reform. The Egyptian Authority for Unified Procurement, Medical Supply and the Management of Medical Technology (UPA) is one of them and was established to support strategic procurement using HTA.Methods: Description of the development of HTA in Egypt supported by a literature search as part of a scoping exercise, and a stakeholder analysis and identification of HTA capacity survey, based on previous surveys, with relevant stakeholders conducted in 2022. This was followed by a stakeholder event where results were shared and further contextualized.Results: The UPA is expected to evaluate the cost-effectiveness of health technologies and public health programs. The HTA process is being developed, focusing on the assessment of the value of new pharmaceuticals being introduced to the Egyptian market. A total of 16 participants responded on behalf of their organizations to the stakeholder analysis and identification of HTA capacity survey. More than 80% of the respondents were familiar with current efforts conducted by UPA and strongly support the implementation of HTA in Egypt. Transparency was highlighted as an important criterion. Over 90% of the respondents mentioned economic analyses as an HTA product being developed in Egypt, and medicines were the type of technology that stakeholders ranked as first in the rank of health technologies that need the output from HTA urgently. Capability building and training were highlighted as areas in which further support is required.Conclusion: This study represents the first attempt to describe the current path for HTA in Egypt. There seems to be momentum in Egypt to proceed and advance with HTA institutionalization. It would be important that next steps are built on the skills and capabilities already in place in Egypt, ensure methods and processes are in place and up to date and involve the wider system in Egypt so stakeholders can appropriately contribute and participate in the HTA process.